Kohesi Pada Lirik Lagu Grup Band Gigi Dalam Album Religi "Mohon Ampun" Dan Implikasinya Dalam Pembelajaran Menulis Puisi - Wahyuni, Sri, Drs. Andi Haris Prabawa, M.Hum (2016)
This research aims to (1) mention lexical and grammatical cohession in song's lyrics of Gigi's religion album, "Mohon Ampun" and (2) describe the implication of the result of analysis of cohession in song lyrics of Gigi's religion album, "Mohon Ampun" in writing poetry learning proccess. The theory which is used as reference to analyze the practice of discourse analysis in this research is Sumarlan in his book entitled Teori dan Praktek Analisis Wacana (2009). This research is a qualitative descriptive with the subject of the research is song's lyrics of Gigi's religion album, "Mohon Ampun". The instrument which is used in this research is the researcher herself and supported by books of discourse, and also other books thats related to the research. This research uses padan method and agih method in data analysis technique. The result of data analysis presented by using formal presentation technique. Grammatical cohession including: reference, which consists of fisrt person reference, aku, then fisrt person reference left attached ku- and right attached -ku. Plural first person reference, kami, kita. Singular econdary person reference left attached engkau-, kau-, and right attached -mu. Singular third person reference left attached dia, and right attached -nya. Demonstrative (temporal) reference morning, afternoon, and evening. Lexical cohession including, repetition (epistrophic, anaphoric and mesodiplosis). Syllable repetition, 3, 4, 6, 7, 8, 9, 10, 11, 12, 13, 14 and 16 syllables. There is also word and vocal repetition "a", "i" and "u". Synonym such as, datang>< tiba. Antonym such as damai>< perang. Collocation such the use of cinta, damai, sentosa words in a pharagraph, so it supports the unity of the theme in the pharagraph.